Buddhist and Muslim interaction in the post-war of Sri Lanka - Razick, Ahamed Sarjoon; Saujan, Iqbal; Beevi, Seyyath Mohammed Hakeema (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sri Lanka is a small pluralistic state. This is a multi-racial social environment, members of all communities lived in peace and harmony with social integration with one another. Each community practised and its own religious cultural values. This situation has changed aftermath of the government’s victory in the war (1983-2009) against the Liberation Tigers Tamil Elam (LTTE). Now there is a series of tense between the Buddhist and Muslim communities in Sri Lanka. The Buddhist Nationalist Groups (BNGs) have been questioned the social and religious features of the Muslims, and their religious obligations were heavily and unduly questioned via provocations from these respective groups. On this background, the study attempts to explore the religious interaction between Muslims and Buddhists in Sri Lanka. The questionnaire survey used as a key tool, and the semi-structured interview conducted among the Buddhists and Muslims in Sri Lanka. The findings of the study show that the relationship between the two communities is generally seen to be in a healthy state. However, the few notable features have exacerbated the tension between the two communities.